Surrogacy and Heterologous Fertilisation on the move - Tsalidis (Αντώνης Τσαλίδης) Antonios (Bioethica, 2016)
Since the day when the first child was born with the aid of assisted reproduction (Louise Brown), the scientific community has always been interested in the implementation and the application of assisted reproduction methods. Although these methods help people around the globe to become parents, they may cause serious health risks, raising at the same time crucial legal and ethical issues. Moreover, the aforementioned issues deepen further due to the development of "reproductive tourism" since people travel to countries where the law permits the application of methods that are prohibited in their home country, thus circumventing the law. This situation can be perilous for the parties involved and evoke serious social and legal issues. Most major issues will be outlined by this comparative study of Greek and German legislation by examining surrogacy and heterologous fertilisation, a field where most delicate situations arise. Last but not least, the need of a common European legal framework, which will protect the public health and the rights of children and parents, is undeniable.